Switching Regime Beta Analysis of Global Financial Crisis: Evidence from International Public Real Estate Markets. Issue 1 (1st January 2017) - Liow, Kim Hiang; Ye, Qing
Abstract : We examine whether the recent subprime/global financial crisis caused some significant changes in the excess return distribution and volatility spillover, as well as the link between them and the world market for a select group of international public real estate markets from January 6, 2000 to June 25, 2015. Employing univariate and multivariate switching regime beta models, our results suggest that the public real estate markets examined responded significantly to the financial crisis with a significant increase in the volatility parameter compared to normal period. Moreover, the linkages of the public real estate markets with the two world market indices have been altered differently by the financial crisis, and are enhanced in the post-crisis period for the European region. In contrast, the three major Asian public real estate markets display reduced risk spillover effect in the low volatility state from the world market in recent years. Our findings offer important and yet different implications for investors in their pursuit for portfolio diversification and policymakers in contagion management in the Asian and European public real estate and stock markets after a recent major financial crisis.